From twisting to settling down as a nurse in China: a qualitative study of the commitment to nursing as a career - Jiao Ye (BMC Nursing, 2020)
Abstract Background The nurse workforce shortage, partially caused by high work turnover, is an important factor influencing the quality of patient care. Because previous studies concerning Chinese nurse work turnover were predominantly quantitative, they lacked insight into the challenges faced by nurses as they transition from university to their career. A successful transition can result in new nurses’ commitment to the career. As such, this study sought to understand how new nurses commit to the career, and focused on identifying facilitators and barriers to such commitment. Methods This was a qualitative study using a grounded theory design. Through purposive sampling, clinical nurses were recruited from hospitals in Western China to participate in semi-structured interviews. The data was analyzed through coding to develop categories and themes. Results Theoretical saturation was achieved after interviewing 25 participants. The data revealed the ‘zigzag journey’ of committing to the nursing career. The emerging core theme was “getting settled”, indicating that new nurses needed to acclimate to the work reality in the nursing career. By analyzing the data provided by the participants, the researchers concluded that the journey to getting settled in nursing compassed four stages:1) “sailing out with mixed feelings”, 2) “contemplating to leave”, 3) “struggling to stay”, and 4) “accepting the role”. For most participants, nursing was described as a way to earn a living for their family, not as a career about which they felt passionate. Conclusions Committing to the nursing career is a complicated long-term process. There seems to be a lack of passion for nursing among the Chinese clinical nurses participating in this study. Thus, the nurses may need continued support at different career stages to enhance their ability to remain a nurse for more than economic reasons.